Brain donation for schizophrenia research: gift, consent, and meaning. Issue 3 (1st June 2003) - Boyes, M; Ward, P
Abstract : The Neuroscience Institute of Schizophrenia and Allied Disorders's (NISAD) " Gift of Hope " Tissue Donor Program is a volunteer programme for people who wish to donate their brain when they die for neuroscience research into schizophrenia. Organ donation for purposes of research differs from transplant donation in a number of ways, most notably the absence of a single recipient. Within a particular community, however, (people with schizophrenia and their carers) the single recipient is replaced by a sense of shared experience and preventing suffering in others. Donors have an investment in the research.